Increasing Access to Physical Activity Within Low Income and Diverse Communities: A Systematic Review. Issue 6 (July 2019) - Stasi, S.; Spengler, J.; Maddock, J.; McKyer, L.; Clark, H.
Objective: The purpose of this review is to uncover some best practices for increasing access to physical activity opportunities by examining efforts used within low income and diverse communities. The theoretical lens used is from the Active Living by Design (ALbD) Community Action Model, with a focus on the 6 essential practices (health equity focus, community engagement, facilitative leadership, sustainable thinking, culture of learning, and strategic communication) describing how partnerships can guide and sustain meaningful change in a community. Methods: A 2-step process guided the literature search. In step 1, 4 databases (PubMed, Psych INFO, Social Science Citation Index, and Cochrane Library) were searched using Boolean connections and variations in the key terms. Step 2 assessed articles by title, abstract, and full text to determine whether the studies met the inclusion and exclusion criteria guided by Preferred Reporting Items for Systematic reviews and Meta-Analyses guidelines. Additionally, included articles were compared against the 6 essential practices outlined by the ecological framework, ALbD. Results: Of 1775 total articles, 14 studies met inclusion criteria. Most of the studies were case studies located in the United States using several different approaches including, changes in the built environment, implementation of a community-based physical activity program, creating partnerships to leverage resources, and policy change. This review compared the 14 studies against the 6 essential practices of the ALbD model and found 2 studies that met all 6 criteria, and only a few studies meeting more than 2 criteria. Conclusions: Overall, the conclusions are 2-fold, (1) only 14 cases demonstrate success in increasing access to physical activity opportunities, suggesting that more can be done to address inequalities. (2) Of the existing efforts, few utilize crucial components to create a sustainable change in the community. Future research should take into consideration the ALbD ecological framework, the best existing theory for this type of work, to guide the creation and implementation of a sustainable community access effort.